2002
DOI: 10.1143/jjap.41.3758
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Ag–In–Sb–Te Phase-Change Material

Abstract: The Ag-In-Sb-Te system is widely used for phase-change discs such as compact disc rewritable (CD-RW) and rewritable digital versatile disc (DVD+RW). To clarify the effect of Ag and In in the Ag-In-Sb-Te system, we studied the local structure of Ag-In-Sb-Te phase-change material by extended X-ray absorption fine structure (EXAFS). The results suggest that the existence of Ag contributes to the thermal stability of amorphous marks and existence of In contributes to high-speed phase-change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…From one point of view, tellurium is unwanted admixture in silver and has to be removed during refining process [1]. From the other, quaternary Ag-In-Sb-Te system is widely used for making phase-change discs such as compact disc rewritable (CD-RW) and rewritable digital versatile disc (DVD+RW) [2,3]. Binary Ag-Te system is also very important in mineralogy because the knowledge of the phases stability may be useful in the interpretation of the formation of ore deposits [4].…”
Section: Introductionmentioning
confidence: 99%
“…From one point of view, tellurium is unwanted admixture in silver and has to be removed during refining process [1]. From the other, quaternary Ag-In-Sb-Te system is widely used for making phase-change discs such as compact disc rewritable (CD-RW) and rewritable digital versatile disc (DVD+RW) [2,3]. Binary Ag-Te system is also very important in mineralogy because the knowledge of the phases stability may be useful in the interpretation of the formation of ore deposits [4].…”
Section: Introductionmentioning
confidence: 99%
“…It means that the amorphous state will be thermally stabilized by the existence of Ag. 14) However, the appearance of the AgSbTe 2 phase in the crystalline AIST films did not further change the sheet resistance as compared with the crystalline ST films, which indicates the minor effect of the AgSbTe 2 phase on the electrical resistivity.…”
Section: Electrical Properties Of Aist and St Filmsmentioning
confidence: 86%
“…[6][7][8][9][10][11][12][13] Besides, previous studies have reported that SbTe films with Ag and In additives have a higher crystallization temperature and better stability than the SbTe binary system. 14) Hence, this study aims to investigate the electrical properties for both SbTe and AgInSbTe films in association with the microstructural characteristics before and after heat treatment. The differences between SbTe and AgInSbTe films were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy of crystallization for -Sb phase can attribute to the movement of Sb and Te atoms in a short range and the rearrangements in the crystalline structures because the lattice site is occupied by all the constituent elements at random. [20][21][22] The additives of Ag and In have also been proven to increase the activation energy of crystallization. 5,23,24) Consequently, the activation energy of -Sb crystallization can be affected by the following factors: rearrangement of the Sb atoms, diffusion in a short range and the additive atom as an obstacle to the movement of the Sb or Te atoms.…”
Section: Electrical Properties Of Aist Filmsmentioning
confidence: 99%